(untitled) - Maimon, Elaine P. (New York, 2011)
This book integrates coverage of visual rhetoric and writing for college. [It] includes models for the kinds of writing students will be doing in college, as well as guidance on how to understand and use visual information in rhetorical contexts.
Keywords: English language,Anh ngữ thực hành; Rhetoric,Tu từ học